Liquid phase separation in undercooled Cu–Co alloys under the influence of static magnetic fields - Zhao, Dandan; Gao, Jianrong (Philosophical transactions of the Royal Society of London. Series A: Mathematical, physical, and engineering sciences, 2019)
Undercooling of Cu-based alloys often induces metastable liquid phase separation followed by rapid solidification of separated liquids. The rapid solidification can help freeze in the morphology of a higher-melting liquid and eases difficulties in studies of liquid phase separation kinetics. In the present work, the influence of static magnetic fields on liquid phase separation in bulk Cu 84 Co 16 composition was investigated. Inductively melted samples were glass-fluxed, undercooled and solidified under uniform and non-uniform magnetic fields generated by a superconducting magnet. Solidification microstructure of the phase-separated samples was examined using an optical microscope. The imposition of the magnetic fields, both uniform and non-uniform, altered the morphology, segregation pattern and size distribution of Co-rich droplets due to liquid phase separation. The imposition of the non-uniform magnetic fields with positive and negative gradients brought about segregation of the Co-rich droplets at the top and the bottom side of the samples, respectively. Such influence of the static magnetic fields is interpreted by assuming intensification of convective flow and Kelvin force-controlled migration of the Co-rich droplets. This article is part of the theme issue ‘Heterogeneous materials: metastable and non-ergodic internal structures’.